Students’ Perception of Using Reading Matrix to Enhance EFL Academic Reading Comprehension in Extensive Reading Classes - Syifa Annisa Rismawati; Christianti Tri Hapsari (CV. Pusdikra Mitra Jaya, 2026)
Reading plays an essential role in higher education, particularly in EFL contexts where students are required to comprehend complex academic texts. However, many students experience difficulties due to limited vocabulary, complex sentence structures, and insufficient background knowledge, which often hinder their reading comprehension. To address this issue, the Reading Matrix has been introduced to support students in organizing and processing information. Therefore, this study aims to explore students’ perceptions of using the Reading Matrix in supporting academic reading and to identify the challenges they encounter when completing it. This study employed a descriptive qualitative design, involving university students in an Extensive Reading class. Data were collected through close-ended questionnaires and semi-structured interviews. The findings indicate that the Reading Matrix helps students organize information, compare ideas, identify relationships, focus on key information, connect ideas, and support overall understanding. However, challenges related to vocabulary, sentence complexity, and background knowledge remain. These results suggest that the Reading Matrix is useful, but its effectiveness depends on additional instructional support.